Mechanical Behavior of the Weld Joints of Thick Steel Plates Produced by Various Welding Processes - Bang, HanSur; Bang, HeeSeon; Ro, ChanSeung; Jeong, SuOk (Проблемы прочности, 2015)
The effect of a welding process (electrogas welding (EGW) and flux cored arc welding (FCAW)) on the fracture toughness, CTOD (crack tip opening displacement), and mechanical properties (tensile, bending, impact strengths and hardness) of thick weld joints is examined. The CTOD value of the FCAW weld joints was higher than that of the EGW ones. The fractured welded specimen after the CTOD test reveals ductile and cleavage fractures of the weld joint faces after flux cored arc and electrogas weldings, respectively. The mechanical properties of the EGW welded specimens satisfied relevant classification rules. These results suggest that the EGW process is an effective substitute for the current welding process (FCAW) used for high-strength thick steel plates.